The relationships between thyroid functions of short-term rapid hypothyroidism and blood lipid levels in post-thyroidectomy patients of differentiated thyroid cancer - Yao, Jinming; Zhao, Junyu; Liu, Jing; Jiang, Shan; Guo, Siyi; Xu, Lusi; Zhang, Xinzhong; Sheng, Qiqi; Wang, Kaili; Liao, Lin; Dong, Jianjun (Frontiers in Endocrinology, 2023)
Objective: To explore the relationship between short-term rapid hypothyroidism and blood lipid levels in patients with differentiated thyroid cancer (DTC).Methods: Seventy five DTC patients scheduled to receive radioactive iodine ablation were enrolled. Levels of thyroid hormone and serum lipids were tested at two time points: the euthyroid before thyroidectomy, and the hypothyroid (off thyroxine). Then the collected data were analyzed. Results: Totally 75 DTC patients enrolled, among them, 5o were female (66.67%) and 25 were male (33. 33%), with an average age of 52.24±1.24 years old. The short-term rapid severe hypothyroidism induced by thyroid hormone withdrawal significantly aggravated dyslipidemia, particularly in patients with dyslipidemia before thyroidectomy (All P < 0.01). However, there was no significant differences between blood lipid levels with different thyroid stimulating hormone (TSH) levels. And our study showed significant negative correlations between free triiodothyronine levels and the changes from euthyjroidism to hypothyroidism in total cholesterol (r=-0.31, P=0.03), triglycerides (r=-0.39, P=0.006), high density lipoprotein-cholesterol (HDL-C) (r=-0.29, P=0.042), and significant positive correlations between free thyroxine and the changes of HDL-C (r=-0.32, P=0.027) were identified in females, however, which were not observed in males. Conclusion: Short-term rapids severe hypothyroidism caused by thyroid hormone withdrawal can lead to rapid significant changes in blood lipid levels. It is necessary to pay attention to dyslipidemia and its long-term effects after thyroid hormone withdrawal, especially in patients with dyslipidemia before thyroidectomy. The ClinicalTrial NO. NCT03006289